Microbiological evaluation of the effectiveness of concurrent disinfection of the patient unit in intensive care - Soares, Jéssica Heloiza Rangel; Danelli, Tiago; Tomita, Giovanna Yamashita; Lima, Ana Carolina Souza de; Faggion, Renata Pires de Arruda; Cardin , Stefani Lino; Oliveira, Thilara Alessandra de; Perugini, Marcia Regina Eches; Tacla , Mauren T. G. Mendes; Belei, Renata Aparecida; Kerbauy, Gilselena (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: The health environment can act as a reservoir for microorganisms. For microbiological control, it is necessary to effectively disinfect and to monitor the quality of this process. Aim: To evaluate, through microbial analysis, the effectiveness of concurrent disinfection of the patient care unit of patients receiving intensive care. Outlining: Cross sectional, descriptive, and observational. Microbiological cultures were performed in the patient's unit, before and after concurrent disinfection using 70% ethyl alcohol. The analysis of the cultures was performed by standard methodology. Results: 42 surfaces were investigated. At the time of pre-disinfection, contamination was identified on 26 (62.0%) surfaces, with the touch screen panels of the mechanical ventilators (6040 CFU/mL - 85.7%) being the ones with the highest microbial quantity (6040 CFU/mL - 85.7%), followed by bedside lockers (2380 CFU/mL - 57.1%) and the bed side rails (650 CFU/mL - 42.9%). After disinfection, 65.3% (17) of the surfaces achieved a total reduction in colony count. Implications: The importance of carrying out concurrent disinfection, with 70% ethyl alcohol, on inanimate surfaces with a high degree of contact with hands in the intensive care unit, for the reduction of the microbial load and promotion of a biologically safe environment for the patient was evidenced.